Tools for Objectifying Motor Assessment and Functional Adaptability of Children with SEN in Special Education - Balint Lorand; Caprita Florin Dragos (BRAIN. Broad Research in Artificial Intelligence and Neuroscience, 2023)
The motric activities for children who have special educational needs (SEN) are adapted and individualized to their deficiencies. It is also considered that the development of motor skills facilitates their participation in various educational activities carried out at school, thus providing some learning opportunities. The article analyzes the way motor abilities influence the children with SEN in the school adaptation. The research was conducted between January and February 2022 at the School Center for Inclusive Education Brașov (Romania). The study included 8 subjects with intellectual disabilities (ID) and associated disabilities, with an average age of 5.8 years (SD = 1.3). The motor skills test was performed by applying Movement Assessment Battery for Children, Second Edition (M ABC-2), using evaluation items for balance, manual dexterity and for throwing and catching objects. School functionality was assessed by the School Function Assessment (SFA), through which the ability to perform the physical and cognitive-behavioral tasks of the children concerned was determined. The results obtained showed a significant connection (r= .934) between the variable of motor skills and the variable of school functionality, which leads us to conclude that motor skills can improve the functional adaptation of children with SEN to activities in the school environment.
Keywords: special education needs; motor skills; special education